2004
DOI: 10.1093/ansci/82.2.626
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin supplements on some aspects of performance, vitamin status, and semen quality in boars12

Abstract: The aim of the present study was to determine the effects of dietary supplements of vitamins on vitamin status, libido, and semen characteristics in young boars under normal and intensive semen collection. Sixty Landrace, Yorkshire, and Duroc boars were allocated randomly from 6 to 10 mo of age to one of the following diets: 1) basal diet (industry level) for minerals and vitamins (Control, n = 15); 2) basal diet supplemented with vitamin C (ASC, n = 15); 3) basal diet supplemented with fat-soluble vitamins (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
34
2
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 21 publications
2
34
2
4
Order By: Relevance
“…Nutrition is important for the reproductive performance and some studies reported that supplementation with selenium and vitamin E improved sperm quality in boars (Marin-Guzman et al, 1997; and vitamin E increased the concentration of spermatozoa in semen (Brezezinska-Slebodzinska et al, 1995). However, a recent study showed that supplement of vitamin C or vitamin E for 5 weeks failed to affect the sperm production in young (6-10 months) boars (Audet et al, 2004). Similarly, the effect of vitamin C on the reproduction of boars is also inconsistent (Lin et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition is important for the reproductive performance and some studies reported that supplementation with selenium and vitamin E improved sperm quality in boars (Marin-Guzman et al, 1997; and vitamin E increased the concentration of spermatozoa in semen (Brezezinska-Slebodzinska et al, 1995). However, a recent study showed that supplement of vitamin C or vitamin E for 5 weeks failed to affect the sperm production in young (6-10 months) boars (Audet et al, 2004). Similarly, the effect of vitamin C on the reproduction of boars is also inconsistent (Lin et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Undernutrition delays sexual maturation (Marino and King, 1980), and overnutrition is associated with reduced fertility in overweight men (Sallmen et al, 2006). Experiments in pigs indicate that nutrients are transferred from blood into semen with varying efficiencies that may or may not be associated with changes in sperm function (Audet et al, 2004).…”
mentioning
confidence: 99%
“…Comunmente, el macho reproductor es alimentado con raciones comerciales balanceadas para hembras en gestación o en lactancia, que no cumplen con sus requerimientos nutricionales. Estas restricciones alimenticias que se le imponen al cerdo, pueden llegar a limitar el acceso a micronutrientes (microminerales) requeridos para un óptimo desempeño productivo (AUDET et al, 2004).…”
Section: Introductionunclassified